Small and Medium-Sized Enterprises in the Service Sector in the Conditions of Industry 4.0 and Society 4.0: Evidence from the South-West Region of the Czech Republic - Vacek , Jiří; Dvořáková , Lilia; Skřivan , Lukáš (Economy of Regions, 2022)
The contribution presents results of the research focused on the adaptation of small and medium-sized enterprises (SMEs) in the service sector to technological, economic, social and environmental conditions of Industry and Society 4.0. The main goals of the research were the analysis and evaluation of the current state, preparedness, motivation and needs of SMEs in the sector of knowledge-intensive services for the timely, purposeful and effective implementation of Industry 4.0 methods and tools in the South-West region of the Czech Republic. The methodological approach is based on a mixed research strategy. Qualitative and quantitative methods such as desk research, explanatory and interpretation methods, questionnaire survey, semi-structured interview and evaluation of data and information were used to achieve the research goals. The results document the high current and future need to increase the knowledge and innovation potential of SMEs, the need for changes in the organisation and content of work, the need for changes in the competencies of employees in the context of robotisation, automation and digitisation of business processes. The results demonstrate barriers to access to sufficient internal and external financial resources, as well as a strong interest of SMEs in cooperation with the academic sector and regional authorities in the development of methodological tools for adaptation to new societal conditions and in the interest of the sustainable existence of these enterprises. The direction of future research is oriented towards the creation of a methodology for the adaptation of SMEs to the conditions of Industry and Society 4.0.